MODEL MANAJEMEN SATUAN PENDIDIKAN PONDOK PESANTREN DARUL ISTIQAMAH MAKASSAR - Yunita Rezky Dati Ali; Aris Munandar; Suci Foura; Dewi Asmia Nur; Ahlun Ansar (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2024)
This article aims to analyze the education and coaching system at the Darul Istiqamah Islamic Boarding School in Makassar, as well as the role of Kiai and teachers in managing students. This research uses a qualitative descriptive method involving interviews, observation, and documentation to obtain in-depth data regarding aspects of education in Islamic boarding schools. The research results show that the Darul Istiqamah Islamic Boarding School applies a holistic approach to developing the character and religious knowledge of its students. The role of Kiai and teachers is very significant in directing and guiding students through interactive and participatory teaching methods. In addition, this research identifies the challenges faced in the student admission process and in structuring their social life. The conclusion of this research confirms that the Darul Istiqamah Islamic Boarding School is committed to improving the quality of education while maintaining local religious and cultural values, as well as adapting to current developments. The existence of this Islamic boarding school not only contributes to religious education but also to the formation of the character of students who have noble morals and are ready to make a positive contribution to society.